DINAMIKA BENTANG ALAM DAN PENGARUHNYA TERHADAP ASPEK FISIK LAHAN DAERAH SOLOK –SINGKARAK, PROVINSI SUMATRA BARAT - Santoso Santoso; Ungkap M. Lumbanatu (Jurnal Geologi dan Sumberdaya Mineral, 2010)
The investigated area of Singkarak and surrounding areas belong to Median Graben at Sumatra Fault Zone. Danau Singkarak is one of the bigest lake in west Sumatra, it has a shape of elongate southeast to northwest in direction. Landform arround Danau Singkarak, are represented by Alluvial Fan (F5), River Terrace (F2), Eroded Structural Terrace (S1), Eroded Fault Scarp (S2), and Undulating Fault Hills (S3). Those landforms are known as tectonic origin (endogen). While far away form Danau Singkarak landforms are represented by exogen origin such as Karst Origin (K1, K2), Denudational Origin (D1, D2, D3) and Volcanic Origin (V2). The landforms on east and west side of Danau Singkarak have difference characteristics. On the east side of Danau Singkarak area landform are characterized by fault scarp which has a very steep slope included landslide, while on west side are characterized by aluvial fan with gently slope. Base on the physical character of tectonic landform, the tectonic activity become higher toward Danau Singkarak which is shown by the alluvial fan produced by Sawah Puding Fault (Karang Alluvial Fan, Airhilang Alluvial Fan, and SaningbakarAlluvial Fan) are being actively till present. This activities also characterized by the destructive earthquake occurrences. Non active alluvial fans distributed far away from Danau Singkarak shuch as the Padanglawas Alluvial Fan, Tanjung Sawah Alluvial Fan and Guguk Alluvial Fan. Those alluvial fans are produced by Air Mundak Fault.Keywards: Singkarak Lake, landform, active alluvial fan, non active alluvial fan, exogen, endogen activity.